Analisis Deskriptif Program Siaran “Belajar di RRI” Dalam Mendukung Pola Belajar Daring Untuk Meningkatkan Pengetahuan Di Kalangan Pelajar Kota Medan - Tharisya Shalsadira (Universitas Muhammadiyah Sumatera Utara, 2022)
In this study, the author focuses on discussing how the RRI PRO 2 FM strategy in the Learning broadcast program at RRI maintains its existence even during the current covid-19 period. Research data collection techniques using descriptive analysis such as observation, in-depth interviews, and documentation. Then for the technical analysis of the data used is by way of reduction, data presentation, and data conclusions. In taking the sample, the researcher used a purposive sampling technique, namely sampling with the criteria of 2 people consisting of 1 announcer and 1 program section head. The results of this study are RRI uses three strategies, namely the first Planning Strategy by determining the material to be delivered, assigning broadcasters and determining the schedule, second is the Implementation Strategy, namely the material presented by the teacher using resource persons followed by a question and answer session and discussion between the announcer and the resource person. The third is the Assessment Strategy by setting the success standard of broadcasters and making corrections to broadcast programs in delivering material.In this study, the author focuses on discussing how the RRI PRO 2 FM strategy in the Learning broadcast program at RRI maintains its existence even during the current covid-19 period. Research data collection techniques using descriptive analysis such as observation, in-depth interviews, and documentation. Then for the technical analysis of the data used is by way of reduction, data presentation, and data conclusions. In taking the sample, the researcher used a purposive sampling technique, namely sampling with the criteria of 2 people consisting of 1 announcer and 1 program section head. The results of this study are RRI uses three strategies, namely the first Planning Strategy by determining the material to be delivered, assigning broadcasters and determining the schedule, second is the Implementation Strategy, namely the material presented by the teacher using resource persons followed by a question and answer session and discussion between the announcer and the resource person. The third is the Assessment Strategy by setting the success standard of broadcasters and making corrections to broadcast programs in delivering material.